Дверь в чужую жизнь: [повести] / Галина Щербакова - Щербакова Галина Николаевна (Pocket book, 2010)
Экземпляры: Аб (20130315) / Инвентарный номер: 99443 / Цена: 75.00 / Авт.знак: Щ 61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6